Klinik Pengurusan Hak Cipta dan Hak Merek untuk Dosen dan Mahasiswa Universitas Bina Darma - Ferry Kurniawan; Rasmila Rasmila; Rolia Wahasusmiah; Deni Erlansyah; Rahmat Novrianda Dasmen; Heri Suroyo; Taqrim Ibadi; Ade Kemala Jaya; Oktaviana Karunia Ilahi; Fauzan Azhiman (Universitas Medan Area, 2022)
Intellectual Property Rights (IPR) is one of the things that must be owned by lecturers and students to acknowledge their creations. There are many parts to IPR, as an initial recognition of works, Lecturers and Students at least have Copyright and Brand Rights. This also applies to Bina Darma University, which has a work program to improve IPR from Lecturers and Students through the Directorate of Innovation and Business Incubator (DIIB). Therefore, Community Service (PkM) activities in which the team is a member of DIIB carry out IPR management clinics by introducing Copyright and Brand Rights to Bina Darma University Lecturers and Students. By the Direct Action method, the PkM Team accompanies Participants and directs them to register an account for the Management of Copyright and Brand Rights. As for the 51 participants who attended the clinic, there were 60.8% lecturers and 39.2% students. In addition, it is recorded that 68.6% of all Participants do not have IPR, both Copyright and Brand Rights. During the PkM activity, participants are welcome to ask questions and discuss during direct practice for the submission of Copyright or Brand Rights. From the results of the PkM activities that have been carried out, it was found that 100% of the Participants already have an account for managing Copyright and Brand Rights and 85% have tried to apply for Copyright and also Brand Rights.